Measurement of Concentrated Natural Latex by Parallel Plate Capacitor Technique - ชัยวรากรณ์, สมกรณ์; โรจนสุวรรณ, สุนิตย์; ดอเลาะเซ็ง, ยุสรี (YRU Journal of Science and Technology, 2018)
In this research project, a parallel plate capacitor was used to measure the dry rubber content of concentrated natural latex in term of capacitor. By measuring the input voltage in rang of 1.5-12.0 Volt. The percentages of water blend with natural rubber latex are 10, 20, 30, 40, 50, 60, 70, 80 and 90 by volume, respectively. Change in dielectric constant of natural rubber latex was investigated as a function of dry rubber content (%DRC). Results showed that the deceased dry rubber content was increasing the volume of water. The polynomial relationship between dry rubber content and dielectric constant (k) was obtained with multiple regression coefficients (R 2 ) in rang of 0.963 - 0.9877.